Vibration based health monitoring for automotive engine - Asrul Syaharani Bin Yusof (Kulliyyah of Engineering, International Islamic University Malaysia, 2012)
In this dissertation, a study of vibration signature is investigated and discuss. The vibration signature of different fault is then compared to the normal engine condition. Eleven selected faults have been selected and tested one at a time so that the outcome of the vibration signature can be predicted. The vibration levels are recorded at one point through three different axis of the engine, the axial direction along the crankshaft axis (x-axis), the transverse direction in the horizontal plane and normal to the crankshaft axis (y-axis) and the vertical direction along the cylinder axis (z-axis). In addition to that, the effect of each fault induced on the engine power and torque also is measure and discuss. All the testing is tested on two different load, no load and full load. The results have shown that every fault that applied to the engine will clearly give a higher vibration level compared to the normal condition. Thus, it can conclude that the monitoring of the engine health can be done thru vibration monitoring technique.